Analisis Kepuasan Petani terhadap Penggunaan Pupuk Organik pada Tanaman Padi - I Gusti Made Gama; Rina Oktaviani; Amzul Rifin (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2016)
EnglishDemand for rice as Indonesian main food staple continues increasing along with the population growth. Currently, most of rice production is still supported by use of chemical fertilizers not environmentally friendly. Government through the Minister of Agriculture Regulation No. 40/2007 recommends organic fertilizer application to improve soil condition and fertility as well as to increase inorganic fertilizer efficiency. One of the organic fertilizers which has been widely applied by farmers is Beka-Pomi fertilizer, a package consisting of Beka decomposer and Pomi organic fertilizers. This research aims to analyze Beta-Pomi customers segmentation, customer satisfaction level, and the main factors affecting farmers’ satisfaction as the fertilizer users. Primary data were collected through random survey of 180 paddy farmers using the fertilizer in Central Java, West Kalimantan, and Lampung Provinces in February-June 2016. The data were analyzed using the descriptive, IPA, CHAID, and CSI methods. Results of analysis indicated that the fertilizer users were dominated by farmers of productive age group (76%), Jajar Legowo and Haston planting pattern (90%), with educational level from primary to secondary schools (91%), agriculture as side job (73%), and land tenure less than 1 hectare (61%). Most farmers satisfied with the Beka-Pomi fertilizer performance (CSI = 80.22%). The main determinants of the satisfaction were land area, planting pattern, educational level, product opinion, farmers’ activities, farmers’ interest, absence of side effects, ability to produce paddy above 10 tonnes/hectare and quick response from the officers. To increase Beka-Pomi sales, it is necessary to improve facilities and field officers’ qualities, decrease product price, and appreciate the farmers applying the fertilizer. IndonesianKebutuhan beras sebagai makanan pokok masyarakat Indonesia akan terus meningkat seiring dengan pertambahan jumlah penduduk. Sampai saat ini, sebagian besar produksi padi masih didukung oleh penggunaan pupuk kimia yang tidak ramah lingkungan. Pemerintah melalui Peraturan Menteri Pertanian Nomor 40/2007 merekomendasikan penggunaan pupuk organik untuk memperbaiki kondisi dan kesuburan tanah, sekaligus meningkatkan efisiensi penggunaan pupuk anorganik. Salah satu pupuk organik/hayati yang telah beredar di kalangan petani adalah pupuk Beka-Pomi yang merupakan paket pupuk hayati (decomposer) Beka dan organik Pomi untuk tanaman padi. Penelitian bertujuan menganalisis segmentasi, tingkat kepuasan, dan faktor-faktor utama yang memengaruhi kepuasan petani sebagai konsumen pupuk. Data dikumpulkan melalui survei secara acak pada 180 petani padi yang telah menggunakan pupuk Beka-Pomi di Jawa Tengah, Kalimantan Barat, dan Lampung pada bulan Februari-Juni 2016. Analisis dilakukan dengan metode deskriptif, IPA, CHAID, dan CSI. Penelitian menunjukkan bahwa pengguna pupuk Beka-Pomi didominasi oleh petani kelompok umur produktif (76%), pola tanam Jajar Legowo dan Haston (90%), tingkat pendidikan setingkat SD─SMA (91%), pekerjaan sampingan di bidang pertanian (73%), dan luas lahan kurang dari 1 ha (61%). Petani merasa sangat puas (CSI = 80,22%) pada kinerja pupuk Beka-Pomi. Kepuasan petani dipengaruhi luas lahan, pola tanam, pendidikan, opini produk, aktivitas petani, minat petani, tidak adanya efek samping, kemampuan menghasilkan padi di atas 10 ton/ha, dan respons cepat petugas. Upaya yang perlu dilakukan untuk meningkatkan penjualan Beka-Pomi ialah meningkatkan fasilitas dan kualitas petugas lapangan, menurunkan harga produk, dan mengapresiasi petani pengguna.